Factors That Influence Community Interest In Using E-Money - Qodar, Muhammad Ali; Rahmatiyah, Isna Nor; Hana, Kharis Fadlullah (Journal of Islamic Financial Technology, 2022)
E-money in Indonesia can be said to be the slowest compared to other countries such as Hong Kong and Singapore. In Indonesia, E-Money itself was only known by the public in 2007, while in other countries such as Hogkong and Singapore, E-Money is already familiar with E-Money compared to Indonesia. The purpose of this study is to reveal what factors make people interested in using E-Money. This research uses a descriptive qualitative method. By using the interview method. Collecting data through interviews with the people of Kudus city who use E-Money. The results of this study reveal that people use E-Money seen from factors such as convenience, security, trust, and service features that have a very positive effect on the use of E-Money in the Kudus city community. The conclusions of this study indicate that interest in using E-Money is influenced by the factors of Ease, Trust, Security, and Service Features. The most influential of the four factors is the ease of using E-Money.. Keywords: Interests Using E-Money, E-Money, Ease Factor